Keragaan Pertumbuhan dan Produksi Jagung Hibrida pada Agroekosistem Lahan Kering Iklim Kering Nusa Tenggara Timur - Sitorus, Alfonso; Kotta, Noldy Rusminta Estorina; Hosang, Evert Yulianes (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Sitorus A, Kotta NRE, Hosang EY.Â 2020. Performance of hybrid maize growth and production on dry land and dry climate agroecosystem of east Nusa Tenggara province. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx.Â Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Corn is an important commodity in East Nusa Tenggara (ENT) because it is the main staple food for most people besides rice, but its productivity is still relatively low. One of solution to increase maize productivity is the use of high-yielding hybrid maize varieties, but their performance under dry land and dry climates of ENT is still unknown. The purpose of this study was to determine the performance of various hybrid maize varieties on dry land and dry climate so that it can be used as a reference for farmers in ENT. The assessment was carried out in Oeteta Village, Sulamu District, Kupang Regency in January-April 2020. The hybrid maize varieties studied were Nasa 29, JH 27, JH 37, JH 45, Pertiwi 2, Pertiwi 5, Pertiwi 6, NK212, Pioneer P21, and NK7328 Sumo. The parameters observed were vegetative and generative growth. Data were analyzed using Analys of Variance at significance level 5% and further tested with the Tukey HSD test at significance level 5% to determine the differences between treatments. The results showed that the variety factor had a significant effect on maize production. Corn yields ranged from 5.67 tonnes/ha - 8.35 tonnes/ha with the highest yields on the Nasa 29 variety but not significantly different from Pertiwi 6, NK7328 Sumo, JH 27, and Pertiwi 5 in the Tukey HSD test at significance level 5%. The average B/C ratio for hybrid maize farming was 1.94. Varieties with B/C ratio value above the average consecutively, namely: Nasa 29, followed by Pertiwi 6, NK7328 Sumo, JH 27, and Pertiwi 5. Based on productivity considerations, hybrid maize varieties are well adapted and recommended to dry land and dry climate of ENT is Nasa 29, followed by Pertiwi 6, NK7328 Sumo, JH 27, and Pertiwi 5.